Improving Food Security through Financial Inclusion - Rini Astuti; Djoni Hartono (Faculty of Economic and Business, 2023)
Financial inclusion may accelerate food insecurity reduction, an issue in Indonesia’s development. However, studies examining the relationship between financial inclusion and food security remain inconclusive and scarce in Indonesia. Therefore, this study aims to analyze how strong the relationship between those variables is, both in general and within specific groups. This study mainly used data from the National Socio-Economic Survey (Susenas) 2020. Food security is measured by dietary diversity score (DDS), while financial inclusion is measured by household accessibility to savings and credit. The association between those variables is examined using the Ordinary Least Square (OLS) method. The results show that financial inclusion is positively related to household food security at a significant level, in general, and according to poverty status and location category. Therefore, expanding financial inclusion may be suggested as an alternative to improve food security. JEL Classification: C31, G20, O10 How to Cite:Astuti, R.,& Hartono, D. (2023). Improving Food Security through Financial Inclusion. Etikonomi, 22(1), 15–30. https://doi.org/10.15408/etk.v22i1.26632.